Atomic-layer-deposition-assisted formation of carbon nanoflakes on metal oxides and energy storage application - Guan, Cao (2014)
Nanostructured carbon is widely used in energy storage devices (e.g., Li-ion and Li-air batteries and supercapacitors). A new method is developed for the generation of carbon nanoflakes on various metal oxide nanostructures by combining atomic layer deposition (ALD) and glucose carbonization. Various metal oxide@nanoflake carbon (MO@f-C) core-branch nanostructures are obtained. For the mechanism, it is proposed that the ALD Al2O3 and glucose form a composite layer. Upon thermal annealing, the composite layer becomes fragmented and moves outward, accompanied by carbon deposition on the alumina skeleton. When tested as electrochemical supercapacitor electrode, the hierarchical MO@f-C nanostructures exhibit better properties compared with the pristine metal oxides or the carbon coating without ALD. The enhancement can be ascribed to increased specific surface areas and electric conductivity due to the carbon flake coating. This peculiar carbon coating method with the unique hierarchical nanostructure may provide a new insight into the preparation of ‘oxides + carbon’ hybrid electrode materials for energy storage applications.